Cardiovascular MRI with ferumoxytol. Issue 8 (August 2016) - Finn, J.P.; Nguyen, K.-L.; Han, F.; Zhou, Z.; Salusky, I.; Ayad, I.; Hu, P.
Abstract : The practice of contrast-enhanced magnetic resonance angiography (CEMRA) has changed significantly in the span of a decade. Concerns regarding gadolinium (Gd)-associated nephrogenic systemic fibrosis in those with severely impaired renal function spurred developments in low-dose CEMRA and non-contrast MRA as well as efforts to seek alternative MR contrast agents. Originally developed for MR imaging use, ferumoxytol (an ultra-small superparamagnetic iron oxide nanoparticle), is currently approved by the US Food and Drug Administration for the treatment of iron deficiency anaemia in adults with renal disease. Since its clinical availability in 2009, there has been rising interest in the scientific and clinical use of ferumoxytol as an MR contrast agent. The unique physicochemical and pharmacokinetic properties of ferumoxytol, including its long intravascular half-life and high r1 relaxivity, support a spectrum of MRI applications beyond the scope of Gd-based contrast agents. Moreover, whereas Gd is not found in biological systems, iron is essential for normal metabolism, and nutritional iron deficiency poses major public health challenges worldwide. Once the carbohydrate shell of ferumoxytol is degraded, the elemental iron at its core is incorporated into the reticuloendothelial system. These considerations position ferumoxytol as a potential game changer in the field of CEMRA and MRI. In this paper, we aim to summarise our experience with the cardiovascular applications of ferumoxytol and provide a brief synopsis of ongoing investigations on ferumoxytol-enhanced MR applications.